Physicochemical properties of premium, standard and economic commercial cat foods in Malaysia - Amir Husni Mohd Shariff; Lam C.H.; Soo A.P.; Kumara Thevan Krishnan; Mona, Z. (Universiti Malaysia Kelantan, 2014)
The importation of cat food into Malaysia has been very phenomenal of late. At the moment, there is no clear legislation with regards to the quality and established standards for cat food imported into Malaysia. In this study, 2 cohort of cat food flavoured chicken (dry) and tuna (wet) were sampled. For each cohort, the cat food were categorised into premium, standard and economy. Composite samples were made from each of these categories and analysed. The macro-nutrients Ca, P, Mg, K, Na and Clin the premium, standard and economy dry cat food products are above the recommended values given by The Association of American Feed Control Officials (AAFCO), with some marginal concession recorded for elemental K. For wet cat food, all the studied macro-nutrients were below the recommended values given by AAFCO, with exception of elemental Cl- (in premium wet cat food). It is interesting to note that premium wet cat food, had significantly lower macro-nutrient concentrations compared to standard and economy wet cat food (p<0.05). Therefore, the quality of dry cat food in premium, standard and economy is good. However, the quality of wet cat food in premium, standard and economy is below par from the recommendation of AAFCO.